The Influence of Digital Literacy on the Information Technology Risk Management Capabilities of Lecturers at Private Universities in Bandung City - Elifasa Ndruru Elifasa Ndruru (JURNAL MANAJEMEN RISIKO, 2026)
Abstract Digital transformation in higher education has increased the use of information technology in various academic activities. On the other hand, this development has also given rise to various information technology risks that require adequate management skills from faculty members as the primary users of digital technology. This study aims to analyze the influence of digital literacy on information technology risk management capabilities among faculty members at private universities in Bandung. The results indicate that faculty members’ levels of digital literacy and information technology risk management capabilities fall into the high category. Data analysis reveals a strong positive correlation between digital literacy and information technology risk management capabilities. Digital literacy has been shown to have a positive and significant impact on faculty members’ ability to identify, analyze, mitigate, and monitor information technology risks These findings indicate that improving digital literacy can strengthen lecturers’ ability to address various risks arising from the use of digital technology in the higher education environment. Therefore, enhancing digital literacy competencies should be part of human resource development strategies to support safe, effective, and sustainable digital transformation in higher education. Keywords: Digital Transformation, Digital Literacy, IT Risk Management, Data Security, Private Universities